Pengenalan Teknologi Kecerdasan Artifisial kepada Siswa SMP Muhammadiyah melalui Praktik Pembuatan Model AI Non-Coding - Triawan Adi Cahyanto; Nur Qodariyah Fitriyah (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service activity aims to improve artificial intelligence (AI) literacy among students of SMP Muhammadiyah through a non-coding, practice-based learning approach. The activity was conducted on March 30, 2026, involving 20 junior high school students. Google’s Teachable Machine platform was used to enable students to build AI image classification models without requiring prior programming knowledge. The program consisted of four sessions: introduction to AI concepts, live demonstration, hands-on model creation, and discussion on AI ethics and risks. Results showed that all student groups successfully created AI models capable of recognizing hand gestures (rock-paper-scissors) with a minimum accuracy of 80%, with some groups achieving above 90%. Students demonstrated high enthusiasm and active participation. A learning module was developed for sustainable use by teachers and students. This activity successfully strengthened the partnership between Universitas Muhammadiyah Jember and SMP Muhammadiyah in technology-based education.Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan literasi kecerdasan artifisial (AI) siswa SMP Muhammadiyah melalui pendekatan pembelajaran berbasis praktik non-coding. Kegiatan dilaksanakan pada 30 Maret 2026 dengan melibatkan 20 siswa. Platform Teachable Machine dari Google digunakan agar siswa dapat membuat model klasifikasi gambar berbasis AI tanpa memerlukan pengetahuan pemrograman sebelumnya. Program terdiri atas empat sesi: pengenalan konsep AI, demonstrasi langsung, praktik pembuatan model, dan diskusi etika serta risiko AI. Hasil menunjukkan seluruh kelompok siswa berhasil membuat model AI yang mampu mengenali gestur tangan (batu-kertas-gunting) dengan akurasi minimal 80%, dan beberapa kelompok mencapai akurasi di atas 90%. Modul pembelajaran telah dikembangkan untuk digunakan secara berkelanjutan oleh guru dan siswa. Kegiatan ini berhasil memperkuat kemitraan antara Universitas Muhammadiyah Jember dengan SMP Muhammadiyah dalam bidang pendidikan berbasis teknologi.